Preliminary Studies on the Synthesis of Redox-Labelled Molecularly Imprinted Nanoparticles in Sensor Development for the Quantification of Perfluoroalkyls in Water - Marco Costa; Sabrina Di Masi; Christopher Zaleski; Sergey A. Piletsky; Cosimino Malitesta (Engineering Proceedings, 2023)
Polyfluoroalkyl compounds (PFASs) are synthetic compounds recently classified as permanent and emerging chemicals ever since their bioaccumulation in humans and the environment, due to the presence of carbon–fluorine functional groups. The design of novel screening tools with addressed high response time for the routine quantification of PFASs in water is highly desirable. In this work, we propose the preparation of a new voltammetric sensor based on molecularly imprinted polymer nanoparticle (nanoMIP) receptors for the highly sensitive and selective quantification of PFASs in water. The nanoMIPs were synthesized by the solid phase approach and immobilized onto functionalized screen-printed platinum electrode (SPPtE), chosen as the transduction element for sensor development. Dimensional characterization of nanoMIPs by Dynamic light scattering (DLS) shows small nanosized imprinted particles (<200 nm) with a polydispersity index (PDI) below 0.3. Electrochemical techniques were used for sensor preparation, characterization, and to assess the analytical performance, respectively. Preliminary calibration curves of nanoMIP-based sensors in a wide range of PFAS concentrations (1.5–100 ng/mL) exhibited high sensitivity toward its target.